2011
DOI: 10.1103/physrevb.84.134519
|View full text |Cite
|
Sign up to set email alerts
|

Greenberger-Horne-Zeilinger generation protocol forNsuperconducting transmon qubits capacitively coupled to a quantum bus

Abstract: We propose a circuit quantum electrodynamics (QED) realization of a protocol to generate a Greenberger-Horne-Zeilinger (GHZ) state for N superconducting transmon qubits homogeneously coupled to a superconducting transmission line resonator in the dispersive limit. We derive an effective Hamiltonian with pairwise qubit exchange interactions of the XY type,g(XX + Y Y ), that can be globally controlled. Starting from a separable initial state, these interactions allow to generate a multi-qubit GHZ state within a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…For the past years, based on circuit QED, much process has been made on entanglement generation with SC qubits. For instance, using SC qubits coupled to a single cavity or multiple resonators (hereafter, the terms cavity and resonator are used interchangeably), a number of theoretical proposals have been presented for realizing entangled states of SC qubits [10][11][12][18][19][20][21][22][23]. Moreover, various two-qubit or three-qubit entangled states have been experimentally demonstrated with superconducting qubits based on circuit QED [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the past years, based on circuit QED, much process has been made on entanglement generation with SC qubits. For instance, using SC qubits coupled to a single cavity or multiple resonators (hereafter, the terms cavity and resonator are used interchangeably), a number of theoretical proposals have been presented for realizing entangled states of SC qubits [10][11][12][18][19][20][21][22][23]. Moreover, various two-qubit or three-qubit entangled states have been experimentally demonstrated with superconducting qubits based on circuit QED [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…As is well known, high-dimensional (HD) quantum entanglement is not only of great interest in providing an additional way for the fundamental tests of quantum nonlocality, but also central for HD-based quantum computation, quantum communication, quantum error correction, and quantum simulation. Over the past years, base on cavity or circuit QED, a large number of theoretical methods have been presented for creating two-qubit or multi-qubit entangled states with various physical systems (e.g., atoms, nitrogen-vacancy centers, quantum dots, and SC devices) [10][11][12][18][19][20][21][22][23][32][33][34][35][36][37][38][39]. However, after a deep search of the literature, we found that based on cavity QED or circuit QED, how to create entangled states of qutrits or higher-dimensional quantum systems with natural or artificial atoms has been rarely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade, a great deal of efforts has been devoted to generating GHZ states in various physical systems. For example, based on cavity or circuit QED, many theoretical methods have been presented for generating multiqubit GHZ states with atoms [12], quantum dots [13,14], and superconducting qubits [15][16][17][18]. A natural question on how to store the prepared GHZ states and how to protect them against decoherence would become interesting and important.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, proposals for generating entangled states with SC qubit circuits have been presented [58]. In addition, based on cavity QED or circuit QED, a large number of theoretical methods have been presented for creating multi-qubit GHZ states with various physical systems (e.g., atoms, quantum dots, and SC devices) that are coupled to a single cavity/ resonator mode [59][60][61][62][63][64][65][66][67][68]. However, we note that how to generate GHZ states with qubits in different cavities has not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%